APLIKASI SIG UNTUK MEMAHAMI FENOMENA TUTUPAN LAHAN DENGAN CITRA SATELIT - Prayogo, Teguh (Jurnal Teknologi Lingkungan, 2007)
Seasonal characteristics of vegetation, such as growing season are closelyrelated to characteristics of the lower atmosphere, and are thereforeimportant variables in global models and vegetation monitoring. NormalizedDifference Vegetation Index (NDVI) data derived from the National Oceanicand Atmospheric Administration’s (NOAA) Advanced Very High ResolutionRadiometer (AVHRR) satellite sensor offer a means of efficiently andobjectively evaluating vegetation response over large geographic areas.Those vegetation responses were computed based on time-series NDVIdata collected from May 1997 to April 1998 over South East Asia. Measureof growing season was computed and analyzed for land cover type. It isdifficult if not impossible to objectively define an absolute the time of thegrowing season from satellite observations. The purpose of this paper isto determine the threshold of the growing season by using GeographicInformation System (GIS).